Skrining Senyawa Metabolit Sekunder Ekstrak Metanol Biji Alpukat (Persea Americana Mill.) Asal Pulau Timor - Aloisius Masan Kopon; Anselmus Boy Baunsele; Erly Grizca Boelan (Akta Kimia Indonesia, 2020)
Avocados (Persea americana Mill.) have many benefits for traditional medicine especially in East Nusa Tenggara. The purpose of this study was to analyze the secondary metabolite compounds contained in avocado seeds and to identify groups compounds in avocado seeds extract. The research method used was maceration of samples for 3 days and continued with phytochemical dan FT-IR test. The result showed that methanol extract of avocado seeds contains phytochemicals based on test result of secondary metabolites, the alkaloids, flavonoids, steroids, terpenoids, saponins and tannins. While the results of FT-IR analysis showed the presences of OH, CH, C=C, and C-O groups.